Health Information Exchange: A Novel Re-linkage Intervention in an Urban Health System. (9th October 2019) - Sharp, Joseph; Angert, Christine D; Mcconnell, Tyania; Wortley, Pascale; Pennisi, Eugene; Roland, Lisa; Mehta, C Christina; Armstrong, Wendy S; Shah, Bijal; Colasanti, Jonathan A
Abstract: Background: Public health information exchanges (HIEs) link real-time surveillance and clinical data and can help to re-engage out-of-care people with HIV (PWH). Methods: We conducted a retrospective cohort study of out-of-care PWH who generated an HIE alert in the Grady Health System (GHS) Emergency Department (ED) between January 2017 and February 2018. Alerts were generated for PWH who registered in the GHS ED without Georgia Department of Public Health (GDPH) CD4 or HIV-1 RNA in the prior 14 months. The alert triggered a social work (SW)–led re-linkage effort. Multivariate logistic regression analyses used HIE-informed SW re-linkage efforts as the independent variable, and linkage to care and 3- and 6-month viral suppression (HIV-1 RNA < 200 c/mL) as primary outcomes. Patients admitted to the hospital were excluded from primary analysis. Results: One hundred forty-seven out-of-care patients generated an alert. Ninety-eight were included in the primary analysis (mean age [SD], 41 ± 12 years; 70% male; 93% African American), and 20 received the HIE-informed SW intervention. Sixty percent of patients receiving the intervention linked to care in 6 months, compared with 35% who did not. Patients receiving the intervention were more likely to link to care (adjusted risk ratio [aRR], 1.63; 95% confidence interval [CI], 0.99–2.68) and no more likely to achieve viral suppression (aRR, 1.49; 95% CI, 0.50–4.46) than those who did not receive the intervention. Conclusions: An HIE-informed, SW-led intervention systematically identified out-of-care PWH and may increase linkage to care for this important population. HIEs create an opportunity to intervene with linkage and retention strategies.